Integrating Emotional Intelligence and Digital Literacy in Hybrid Workforces: Evidence from Bali’s Multidisciplinary Management Landscape - Suastama, Ida Bagus Radendra (Forum Manajemen, 2025)
The rise of hybrid work in post-pandemic Bali—driven by digital transformation in tourism, finance, and creative industries—has intensified demands for managers who can navigate both technological and interpersonal complexities. While emotional intelligence (EI) and digital literacy (DL) are recognized individually, their combined role across management subdomains remains underexplored, particularly in island economies with distinct socio-cultural dynamics. This study addresses this gap by examining how the synergy between EI and DL enhances managerial effectiveness among professionals in Bali across five management fields: Financial Management, Marketing Management, Human Resource Management, Office Management, and Tourism and Secretarial Business Management. Using a mixed-methods approach with data from 312 managers employed in Balinese organizations—including hotels, SMEs, financial cooperatives, and private educational institutions—we find that integrated EI–DL capabilities significantly predict adaptive leadership, team cohesion, and service innovation. Qualitative insights reveal context-specific practices such as “digital gotong royong” (collaborative digital workflows) and empathetic virtual client handling rooted in Balinese values of harmony (Tri Hita Karana). The study proposes a culturally attuned, multidisciplinary management framework with implications for leadership development in island and emerging economies.   Peningkatan kerja hybrid di Bali pasca-pandemi—yang didorong oleh transformasi digital di sektor pariwisata, keuangan, dan industri kreatif—telah meningkatkan permintaan akan manajer yang mampu mengelola kompleksitas teknologi dan interpersonal. Meskipun kecerdasan emosional (EI) dan literasi digital (DL) diakui secara terpisah, peran gabungan keduanya di berbagai subbidang manajemen masih kurang dieksplorasi, terutama di ekonomi pulau dengan dinamika sosial-budaya yang unik. Studi ini mengatasi kesenjangan tersebut dengan menganalisis bagaimana sinergi antara EI dan DL meningkatkan efektivitas manajerial di kalangan profesional di Bali di lima bidang manajemen: Manajemen Keuangan, Manajemen Pemasaran, Manajemen Sumber Daya Manusia, Manajemen Kantor, dan Manajemen Bisnis Pariwisata dan Sekretariat. Menggunakan pendekatan campuran dengan data dari 312 manajer yang bekerja di organisasi Bali—termasuk hotel, UMKM, koperasi keuangan, dan lembaga pendidikan swasta—kami menemukan bahwa kemampuan EI–DL yang terintegrasi secara signifikan memprediksi kepemimpinan adaptif, kohesi tim, dan inovasi layanan. Wawasan kualitatif mengungkapkan praktik-praktik yang spesifik konteks, seperti “digital gotong royong” (alur kerja digital kolaboratif) dan penanganan klien virtual yang empati, yang berakar pada nilai-nilai Bali tentang harmoni (Tri Hita Karana). Studi ini mengusulkan kerangka kerja manajemen multidisiplin yang sensitif secara budaya, dengan implikasi untuk pengembangan kepemimpinan di ekonomi pulau dan negara berkembang.